DOMESTIKASI KEKERASAN SIMBOLIK DI SEKOLAH: PERSPEKTIF SOSIOLOGI PENDIDIKAN - I Ketut Suda (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
This article intends to examine the symbolic violence that occurs in schools seen fromthe perspective of educational sociology. This is interesting, because many people are not awarethat school textbooks, especially Electronic School Books (BSE) contain symbolic violence, namelysubtle violence, but behind it contains coercive domination. This study uses a qualitative approachwith critical analysis (critical emotional knowledge paradigm). The findings obtained in theform of symbolic violence in schools occur through the forced dominance in the form ofillustrations in school textbooks, such as the use of language and dominant class symbols. Exampleof using the term 'sightseeing' which is actually an upper class habitus to dominate studentsfrom the lower classes. Likewise, the introduction of objects that are familiar with the upperclasses of society such as refrigerators, vacuum cleaners, TVs, etc. as illustrations in schooltextbooks is a form of symbolic violence carried out in a very subtle way. The way to domesticatesymbolic violence that occurs in schools is that teachers must reduce the intensity of the use ofdominant class symbols in providing illustrations of lessons in school. Another way is for teachersto also try to use the illustrations of the dominant and lower classes proportionally in explainingthe subject matter.